Pengaruh Penggunaan Model Pembelajaran Tipe The Power Of Two Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Sejarah Kelas XI SMA N 1 Koto Baru Dharmasraya - Susanto, Herdi; Zafri, Zafri; Nurhuda, Ahmad (Pendidikan Sejarah, 2013)
ABSTRACTLow ability students understanding of the interpretation of facts is caused by various factors one of which is the process of teaching history is still a student information delivery is only able to make keeping in, the purpose of learning the history of one of them is to train students to think critically through the facts in the teaching of history. One effort to improve understanding of the interpretation of the facts in the model of teaching history through The Power Of Two. This study aimed to determine the effect of the application of The Power Of Two models of the learning outcomes of students in high school history Koto Baru Sma N 1 Dharmasraya. Benefits of this research is to encourage history teachers to innovate in using learning model that can improve the learning outcomes of students in finding their own historical core subject matter .This research is quantitative research, in which data is obtained through direct experimentation in class XI IPS SMA Negeri 1 Â Koto Baru Dharmasraya. The selection of the sample in this study was taken by Random Group assuming that each group has the ability to learn the history and customs of the same. Sampling was done by two classes, for the experimental class XI IPS 3 and a control class is class XI IPS 4.After a study found that the study results to interpret historical facts experimental achievement of a higher class than the control class. This is evident from the difference value of 8.34 posttest experimental class and the control class posttest score difference at 6.93 thus increasing learning outcomes interpretation of historical facts experimental class higher than the control class learning outcomes.From the analysis of the results of research and discussion, it can be concluded that the application of learning models The Power Of Two influential real significant impact on student learning outcomes in interpreting historical facts subject matter of class XI IPS SMA Negeri 1 Koto baru Dharmasraya.Keywords: IenfluenceÂÂ â The Power Of Two - Result study